(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: Corona virus is a new pathogen of high contagious abilities. Pregnant women are at an increased risk due to physiologic changes in their immune, cardiopulmonary and coagulation systems. This study was designed to evaluate the fetomaternal outcome of the pregnant patients with COVID-19. Methods: This retrospective observational study was conducted in CMH Dhaka from May 2020 to July 2020. Total 81 hospitalized pregnant patients with confirmed COVID-19 were enrolled. Relevant data were recorded in a preformed data collection sheet and analyzed by SPSS version 20. Results: Total patients were 81 with a mean age of 27 years; 49.1% were in third trimester, 83% were in 35-40 weeks of gestation and 48% were asymptomatic. Common symptom severe cough (26%) and fever(14%); 7.4% patients had multiorgan failure, 81% hadlymphopenia, 7.4% patients under went chest CT and had in filtrates in both lungs. Mild to moderate disease was common and 7.4 % had severe disease, 3.7% needed mechanical ventilation. There was a single maternal death. Most (92.6%) patients were treated in Corona ward and 7.4% in Corona HDU and ICU. There were 3 spontaneous abortions; 64.2% delivered during the study period, 80.8% underwent a Caesarean section, 2.4% had hysterotomy, 15.1% underwent normal vaginal delivery (NVD), 15.4% patients underwent premature termination of pregnancy. Ongoing pregnancy was 26 (32.1%).Four neonates were found COVID-positive. There was 47 livebirths, 3 intrauterine deaths (IUD) and 2 neonatal deaths. Their hospital stay was 13.1 days (SD±6.37).Mean interval of breastfeeding was 13.3 days (SD±6.44). Conclusion: From the study findings, it can be concluded that, COVID-19 had adverse fetomaternal outcomes. COVID-19 pandemic has exerted immense stress on health care system. With this study we can further modify our treatment strategy and reduce the load on our health system. J Bangladesh Coll Phys Surg 2021; 39(2): 100-105